ANALISIS PEMAHAMAN KONSEP SUHU DAN KALOR MENGGUNAKAN INSTRUMEN THERMAL AND TRANSPORT CONCEPT INVENTORY BERBASIS REPRESENTASI GRAFIK PADA SISWA SMAN 1 GAS - Siti Maisyaroh; Fakhruddin '; Nur Islami (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this research is to analyze the understanding of the temperature and heat materials concept using TTCI instruments (Thermal and Transport Concept Inventory) based on graphical representation. The method in this study was a survey technique was done through writtenl questions of understanding concept test. The population was all students of class X SMA Negeri 1 GAS and sampled using simple random sampling with the number of samples of 92 students. Data was collected with TTCI instrument equipped with CRI. Data were analyzed descriptively to determine the level of understanding of students' concept of temperature and heat matter. The result shows that the average score of the percentage of the most dominant learners are in the category unknow concept with the percentage of 45.28%, while the percentage of learners who understand the concept is 13.04%, misconception is 27.09%, And guess the answer is 14.56%. This shows that the students' understanding of the temperature and heat materials based on graphic representations is still that is revealed from the understanding of learners is still below 30%.Keyword: conceptual understanding, misconceptions, temperature and heat.